Genetic modulators of Plasmodium falciparum parasites asexual fitness and resistance to clinical and preclinical compounds - Hong, Davin (Nanyang Technological University, 2023)
Emergence of malarial Plasmodium falciparum KEL1/PLA1 co-lineage in Southeast Asia caused the failure of dihydroartemisin+piperaquine (DHA+PPQ). PfKelch (k13) C580Y mutation and plasmepsins 2/3 gene (pm2/3) amplification, markers of DHA and PPQ resistance respectively, are hallmarks of KEL1/PLA1 parasites such as RF7, while PPQ resistance marker, M343L mutation in pfcrt on a mutant pfcrt Dd2 background, also emerged. Interactions between pfcrt M343L mutation and multicopy pm2/3 to confer PPQ resistance and the impact of KEL1/PLA1 hallmarks on parasite asexual fitness has not been elucidated. By using CRISPR/Cas9 editing and limiting dilution cloning of RF7 parasite and its drug-sensitive NF54 cross progeny, we illustrate the importance of pfcrt M343L background in PPQ resistance with pm2/3 amplification augmenting the phenotype. M343L mutation, however, did not confer resistance to artemisinin partner drugs lumefantrine or mefloquine, while pm2/3 amplification augmented resistance phenotype to preclinical compound MMV675939. Drug-free long-term competitive fitness assays between RF7 clones revealed that multicopy pm2/3 on mutant k13 led to moderate parasite fitness defect. These results confirmed DHA+PPQ selects for pm2/3 amplification and mutant k13/pfcrt parasites, allowing RF7 to emerge, but poor fitness in absence of PPQ can deamplify pm2/3. Current parasite genotypes reinforced the appeal of artesunate+mefloquine as a DHA+PPQ replacement.